Absenteísmo docente em duas escolas do distrito Jardim Ângela do Município de São Paulo - Jacinto, Gabriel José (2016)
This research analyzes the docent absenteeism in two schools in the district of Jardim Angela at the town of São Paulo. This theme was developed as a study object for its importance in everyday school life. It is about listening to the docents about the absenteeism and try to comprehend the explanations that they give to absences on school days and the school actions to manage such absences. The research is developed in two schools of the state public education system located within the same territory. The choice of one of them is due for its location in an area of better access and with good material conditions; And the other one was chosen for being located in an area with worse material conditions and difficult acces, which interest us to better analyze the territory factor in a relation with the school. The teachers interviewed are from 9th grade of Elementary School I of Portuguese language and mathematics disciplines once the workload is heavier on their curriculum. Teachers of 9th grade of Elementary School I of foreign language discipline were also interviewed due to the reduced workload and, for being often seen as superfluous. The 9th grade was chosen for being the year of conclusion of cycle 2 and because of the assessment of Saresp. Absences were researched between school years of 2013 and 2014, by the accessibility of informations of two institutions. The research was conducted by the analysis of documents with the teachers' absenteeism recording and the interviews with teachers of respective subjects. The study was based on territory and territoriality definitions according to Haesbaert, it applied ideas of Nóvoa on the docent profession, on Tardif about the reflection of docent knowledge and the characteristics of docent work and the school social role approached by Sacristan